Drying methods affected the fatty acids oxidation and bacterial community of traditional dry-cured ducks during processing and its relation with the aroma formation - Linyue Qi; Liangwei Xu; Hongbing Chen; Haixing Li; Yikui Lai; Xiaohua Liu (Poultry Science)
The formation of volatile compounds in dry-cured ducks produced by hot and cold air circular drying (HCAD), hot air drying (HAD), and traditional sun drying (TSD) were analyzed by E-nose and GC-MS. The HCAD exhibited higher alcohols, aldehydes, esters, and furans than that of the other two. Six, five, and three key compounds were identified by OAV in HCAD, HAD, and TSD, respectively. Nonanal was the highest relative content of aldehydes in all groups. (E)-2-octenal was detected only in HCAD. HAD accelerated the oxidation of fatty acids. The POV and AV of HAD were 0.24 g/100 g and 2.02 mg/g when stored for 15 days, which were higher than that of HCAD and TSD. Proteobacteria, Actinobacteriota and Firmicutes were the most abundant phylum, Psychrobacter, Kocuria, and Macrococcus were the primary dominant genus. The hightest abundance of Firmicutes and Macrococcus in the HCAD-15d might contribute to the aroma formation. HCAD showed a better quality and flavor than TSD and HAD, indicating it is an innovative method for producing dry-cured duck.